Potential Survival Benefit of Anti-Apoptosis Protein: Survivin-Derived Peptide Vaccine with and without Interferon Alpha Therapy for Patients with Advanced or Recurrent Urothelial Cancer—Results from Phase I Clinical Trials. (20th November 2013) - Tanaka, Toshiaki; Kitamura, Hiroshi; Inoue, Ryuta; Nishida, Sachiyo; Takahashi-Takaya, Akari; Kawami, Sachiyo; Torigoe, Toshihiko; Hirohashi, Yoshihiko; Tsukamoto, Taiji; Sato, Noriyuki; Masumori, Naoya
Abstract : We previously identified a human leukocyte antigen (HLA)-A24-restricted antigenic peptide, survivin-2B80–88, a member of the inhibitor of apoptosis protein family, recognized by CD8+cytotoxic T lymphocytes (CTL). In a phase I clinical trial of survivin-2B80-88 vaccination for metastatic urothelial cancer (MUC), we achieved clinical and immunological responses with safety. Moreover, our previous study indicated that interferon alpha (IFN α ) enhanced the effects of the vaccine for colorectal cancer. Therefore, we started a new phase I clinical trial of survivin-2B80–88 vaccination with IFN α for MUC patients. Twenty-one patients were enrolled and no severe adverse event was observed. HLA-A24/survivin-2B80–88 tetramer analysis and ELISPOT assay revealed a significant increase in the frequency of the peptide-specific CTLs after vaccination in nine patients. Six patients had stable disease. The effects of IFN α on the vaccination were unclear for MUC. Throughout two trials, 30 MUO patients received survivin-2B80–88 vaccination. Patients receiving the vaccination had significantly better overall survival than a comparable control group of MUO patients without vaccination ( P = 0.0009 ) . Survivin-2B80–88 vaccination may be a promising therapy for selected patients with MUC refractory to standard chemotherapy. This trial was registered with UMIN00005859 .